FAMILIAS DISFUNCIONALES Y SU INCIDENCIA EN EL PROCESO DE ENSEÑANZA APRENDIZAJE DE LOS ESTUDIANTES DEL PRIMER AÑO DE EDUCACIÓN GENERAL BÁSICA PARALELO G DE LA UNIDAD EDUCATIVA LA MANA DEL CANTÓN LA MANA - Acurio Valencia, Delia Fernanda (2024)
In education, family participation is essential. Parents must play the role of counselors for their children, strengthening their knowledge through educational activities. However, the various difficulties that arise in the family environment today can restrict children's learning. The objective of this study is to analyze dysfunctional families and their impact on the teaching-learning process of students in the First Year of General Basic Education Parallel G of the La Mana Educational Unit of the La Mana Canton. To do so, a qualitative approach is used; the methods used have been inductive-deductive, logical-historical and analysis- synthesis. This scientific article is based on a documentary review. The survey carried out on teachers, parents and students of the educational institution reveals significant concerns about the impact of dysfunctional families on the academic performance and emotional well- being of students. The results show a description of theoretical concepts related to the generalities of learning, learning skills and the role of the family in early education, as well as an analysis of the characteristics, types, dimensions and subdimensions of dysfunctional families. In conclusion, the conflicts typical of dysfunctional families prevent children from consolidating knowledge, sharing experiences and developing learning skills.